SOME CONTRIBUTION OF SOFT RUGULAR OPEN SETS TO SOFT SEPARATION AXIOMS IN SOFT QUAD TOPOLOGICAL SPACES - Arif Mehmood Khattak; Asad Zaighum; Muhammad Ishfaq; Shamoona Jbeen; Iqrar Hussain (Journal of New Theory)
Our main interest in this study is to look for soft regular separations axioms in soft quad topological spaces. We talk over and focus our attention on soft regular separation axioms in soft quad topological spaces with respect to ordinary points and soft points. Moreover study the inherited characteristics at different angles with respect to ordinary points and soft points. Some of their central properties in soft quad topological spaces are also brought under examination.